Results of the Japanese kanji trial class aimed at the independent and creative activities of students (Mongolian Journal of Humanities and Social Sciences, 2024)
This article introduces the planning, implementation, and results of the trial class of "Japanese kanji" organized within the context of "Elementary Japanese Kanji for Japanese Language Learners in Mongolia" textbook. The trial class was organized with the aim of exploring the independent and creative activity of students.At the beginning of the trial class, "Thematic lesson plan" and "Independent work guidelines" were presented to the students for common understanding of the lesson of both the teacher and the students. During the class, the homework and independent work completed by the students were studied by sampling, analyzing and summarizing as the subject of the trial class.As a result of the class, the students were trying to express themselves using the kanji studied in the lesson, and in a few instances, with kanji that were not learnt. In addition, it was observed that they use kanji appropriately at the sentence, body, and text level, and learn the meaning and use of kanji, as well as grammar and expression skills. The students gradually acquired the skills and practice of writing within the given topic, and the size of the text continuously increased. Therefore, we conclude that the trial lesson aimed at the independent and creative activities of the students was effective.Оюутны бие даасан, бүтээлч үйл ажиллагааг дэмжсэн япон хэлний ханзны туршилт хичээлийн үр дүнХураангуй: Энэхүү өгүүллээр “Монголын япон хэл суралцагчдад зориулсан Япон хэлний ханз Анхан шат” сурах бичиг ашиглан зохион байгуулсан “Япон хэл ханз” туршилт хичээлийн төлөвлөлт, хэрэгжилт, үр дүнг танилцуулах болно. Бид оюутны бие даасан, бүтээлч үйл ажиллагааг зорьж уг туршилт хичээлийг зохион байгуулсан. Туршилт хичээлийн үр дүнд оюутан хичээлээр судалсан ханз, цөөн тохиолдолд судлаагүй ханзыг ч хэрэглэж япон хэлээр бичиж илэрхийлэх оролдлого хийж байлаа. Мөн тэд ханз үсгийг өгүүлбэр, цогцолбор, эхийн түвшинд зохистой хэрэглэж, оролтоос ханзны утга, хэрэглээг сурахаас гадна дүрэм, бичих чадварт ч суралцаж байгаа байдал ажиглагдсан. Цаашлаад оюутан өгөгдсөн сэдвийн хүрээнд бичих чадвар, дадалд бага багаар суралцаж, бичвэрийн хэмжээ аажим аажмаар томорч байв. Иймд бид оюутны бие даасан, бүтээлч үйл ажиллагааг зорьсон уг туршилт хичээл үр дүнтэй болсон хэмээн дүгнэж байна.Түлхүүр үг: оролт, гаралт, JF стандарт, ханз үсэг, хэрэглээ